2021
DOI: 10.3390/ijms22063228
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Small: Small Molecules as Potential Synergistic Adjuncts to Checkpoint Inhibition in Melanoma

Abstract: Metastatic melanoma remains the deadliest form of skin cancer. Immune checkpoint inhibition (ICI) immunotherapy has defined a new age in melanoma treatment, but responses remain inconsistent and some patients develop treatment resistance. The myriad of newly developed small molecular (SM) inhibitors of specific effector targets now affords a plethora of opportunities to increase therapeutic responses, even in resistant melanoma. In this review, we will discuss the multitude of SM classes currently under invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…Our previous study revealed that two vitamin D analogs, calcitriol and low calcemic calcipotriol, exhibited modulatory on the A375 melanoma cells treated with dacarbazine, decreasing the half maximal inhibitory concentration (IC50, calcitriol only) for the drug, stimulating G1/G0 arrest, and causing a marked decrease in the mitochondrial transmembrane potential under given experimental conditions (30). Since the process of angiogenesis is crucial for growth, progression, and metastasis of the majority of solid tumors, including melanomas (62,63), in the current study, the effects of cediranib, an oral tyrosine kinase inhibitor (TKI) of VEGFR1-3, PDGFR, and c-KIT (64), used in combination either with 1,25(OH) 2 D 3 or with low-calcemic analog calcipotriol, were tested in the same A375 human malignant melanoma cell line, carrying the BRAF V600E mutation, very common in melanoma patients (65), which was shown to be pro-angiogenic in several human tumors (66). Selected experiments were also carried out in MNT-1, RPMI-7951, and SK-MEL-28 melanoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed that two vitamin D analogs, calcitriol and low calcemic calcipotriol, exhibited modulatory on the A375 melanoma cells treated with dacarbazine, decreasing the half maximal inhibitory concentration (IC50, calcitriol only) for the drug, stimulating G1/G0 arrest, and causing a marked decrease in the mitochondrial transmembrane potential under given experimental conditions (30). Since the process of angiogenesis is crucial for growth, progression, and metastasis of the majority of solid tumors, including melanomas (62,63), in the current study, the effects of cediranib, an oral tyrosine kinase inhibitor (TKI) of VEGFR1-3, PDGFR, and c-KIT (64), used in combination either with 1,25(OH) 2 D 3 or with low-calcemic analog calcipotriol, were tested in the same A375 human malignant melanoma cell line, carrying the BRAF V600E mutation, very common in melanoma patients (65), which was shown to be pro-angiogenic in several human tumors (66). Selected experiments were also carried out in MNT-1, RPMI-7951, and SK-MEL-28 melanoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The use of targeted therapies and checkpoint inhibitors have significantly improved long-term outcomes. Although progress has been made in targeting melanoma with pre-requisite genotypes using small molecule inhibitors such as BRAF/MEK inhibitors, most relapse after 6 to 9 months as the majority will develop drug resistance [1]. Furthermore, 40-60% of patients with melanoma have de-novo or acquired resistance to immunotherapy leading Cancers 2021, 13, 4520 2 of 14 to disease progression [2,3].…”
Section: Introductionsmentioning
confidence: 99%
“…In recent years, peptides have displayed excellent potential as inhibitors targeting protein–protein interactions (PPIs) [ 25 , 28 ]. Compared with small molecules [ 29 ], peptide drugs can form a larger binding interface with target proteins, so they have better specificity and binding ability, and are more suitable for PPIs [ 30 ]. Therefore, it is of great significance to study peptide inhibitors for the next generation of immune checkpoint based anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%